Implementation of Islamic Communication Principles in Antiretroviral Adherence Counseling for Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome Patients - Suciati; Abdul Malik; Mohammad Fakhri (UIN Sunan Gunung Djati, 2025)
This study explores the role of Islamic communication principles in enhancing antiretroviral therapy (ART) adherence among HIV/AIDS patients at West Nusa Tenggara Provincial Hospital (NTB), Indonesia, focusing on culturally sensitive counselling techniques. Using a qualitative case study approach, the research involved in-depth interviews and observations with three HIV/AIDS counsellors (K1, K2, and K3) and three patients (P1, P2, and P3) with a history of ART discontinuation. Data were collected through interviews, observations of counselling sessions, and secondary documentation, then analyzed using the Miles and Huberman model, which includes data collection, reduction, presentation, and conclusion drawing. The findings revealed that counsellors (K1, K2, and K3) employed ethical and empathetic communication principles, aligning with the six qaulan (Islamic communication principles): qaulan sadida (truthful speech), qaulan maysura (easy-to-understand speech), qaulan baligha (impactful speech), qaulan ma'rufa (kind speech), qaulan karima (respectful speech), and qaulan layyina (gentle speech). Although counsellors were not explicitly aware of these principles, their practices inherently reflected these values, fostering trust, reducing stigma, and improving patient adherence to ART. Patients (P1, P2, and P3) reported feeling respected, supported, and motivated during counselling, strengthening their commitment to lifelong treatment. This study highlights the importance of integrating Islamic communication principles into HIV/AIDS counselling to align with patients' cultural and religious values, particularly in Muslim-majority settings. This approach enhances ART adherence, strengthens patient-counselor relationships, reduces stigma, and promotes better health outcomes. The findings contribute to culturally competent healthcare practices by advocating for patient-centred counselling strategies that incorporate religious and cultural values, ultimately improving adherence and quality of life for people living with HIV/AIDS.